Job Stress and Job Involvement: A Study of IT Professionals from North India - Walia, Kranti; Narang, Sourabh (Prabandhan: Indian Journal of Management, 2015)
In order to gauge the well - being of professionals working in the IT industry, it is important to measure the levels of job stress experienced by them. This study attempted to ascertain the impact of various elements of job stress on job involvement in the IT sector. The sample for the study consisted of 117 professionals working in IT companies in three regions, that is, NCR region, Delhi, and Chandigarh. The findings highlighted that the sub variables of job stress that showed a significant negative correlation with job involvement were inter role distance, role stagnation, role overload, role isolation, and role ambiguity. In order to increase the job involvement level of employees, steps should be taken to minimize the ill effects of job stress by adopting various measures to enhance their work-life balance. Adopting person-organization-fit approach and offering challenging job roles to employees can be the managerial implications of the study.